Data Mining in Supplier Selection: A Practical Application Using Microsoft SQL Server 2005 - Sunarya, Rajasa Utama (2008)
The practice of Data Mining is widely used in today's information age where data is abundant. Data Mining concepts are applied in many facets of everyday activities in business. The issue of supplier selection has become a crucial decision making problem in every company. Data Mining can become a very useful tool in giving decision makers an easier task when faced with supplier selection problem. This dissertation attempts to show as such by using a popular software package Microsoft SQL Server 2005.